Association between biologic therapy and fracture incidence in patients with selected rheumatic and autoimmune diseases: A systematic review and meta-analysis of randomized controlled trials - Fang Lv; Suiyuan Hu; Chu Lin; Xiaoling Cai; Xingyun Zhu; Linong Ji (Elsevier, 2022)
Objectives: To investigate the effect of biologic therapy on risk of fracture in selected rheumatic and autoimmune diseases. Methods: The PubMed, Cochrane library, and EMBASE databases were systematically searched from the inception dates to June 4, 2021. Randomized clinical trials (RCTs) comparing biological disease-modifying antirheumatic drugs (bDMARDs) with non-bDMARDs or placebo in patients with five selected rheumatic and autoimmune diseases were included. Meta-analyses were conducted to calculate the odds ratio (OR) with 95 % confidence intervals (CIs) for major osteoporotic fracture, hip fracture, osteoporotic non-vertebral fracture, and total fracture. Results: A total of 100 RCTs involving 51,413 participants fulfilled the inclusion criteria. In patients with psoriasis (Ps), and psoriatic arthritis (PsA), compared with placebo or non-bDMARDs therapy, the risk of major osteoporotic fracture (OR, 0.34 [95 %Cl, 0.15-0.76], p = 0.009), hip fracture (OR, 0.22 [95 %Cl, 0.05-0.89], p = 0.03), and osteoporotic non-vertebral fracture (OR, 0.26 [95 %Cl, 0.10-0.62], p = 0.003) were significantly decreased with the use of bDMARDs. In patients with rheumatoid arthritis (RA), axial spondyloarthritis (axSpA), systemic lupus erythematosus (SLE), and inflammatory bowel diseases (IBD), the risk of fracture were not changed with biologic treatment. Conclusions: The existing evidence from RCTs indicated the use of bDMARDs was associated with a low risk of major osteoporotic fracture, hip fracture, and osteoporotic non-vertebral fracture in patients with Ps and PsA. There are still urgent needs for studies regarding the actions of biologic therapies on the risk of bone fractures in systemic inflammatory diseases.